The Effectiveness of Exclusive Breastfeeding Education through Audio-Visual Media and Demonstration among Primiparous Mothers - Pipit Fitriani; Yayat Suryati; Juju Juhaeriah; Ida Maryati; Murtiningsih Murtiningsih (Indonesian Journal of Global Health Research, 2025)
Exclusive breastfeeding is the most optimal source of nutrition for infants during the first six months of life, yet its coverage in Indonesia remains suboptimal, particularly among primiparous mothers. This study aimed to analyze the effectiveness of exclusive breastfeeding education through a combination of audio-visual media and demonstration compared with leaflet-based education. This study employed a quasi-experimental design with a pretest–posttest control group, involving 48 primiparous mothers as research samples determined using the purposive sampling method based on the Slovin formula with a 10% margin of error, recruited from two midwifery practices in West Bogor District. Respondents were equally divided into intervention (audio-visual + demonstration, n=24) and control groups (leaflet, n=24). Data on knowledge, attitudes, and breastfeeding skills were collected using validated questionnaires and observation checklists, then analyzed with Wilcoxon and Mann–Whitney tests at a 5% significance level. The findings revealed that leaflet education significantly improved knowledge, particularly on basic breastfeeding concepts (p<0.05). However, audio-visual and demonstration methods were more effective in transforming attitudes and enhancing psychomotor skills, especially correct positioning and latching techniques (p<0.001). These results highlight that leaflet is useful for reinforcing cognitive understanding, while audio-visual and demonstration approaches provide more interactive and practical learning that supports behavioral change.